THE LEGAL EVOLUTION OF THE GUARANTEE OF WATER LAW IN ECUADOR - Martínez Moscoso, Andrés (2023)
The legal treatment that has been given to water in Ecuador is interesting from the point of view of its constitutional evolution, because although it is true that it was considered a natural resource, it is now treated as a human right and a strategic sector. In the present investigation, based on a historical-legal methodology, a review is made of how the treatment of wáter resources has advanced at a constitutional level, and how international instruments, as well as the jurisprudence of international organizations and the soft law, influenced the Ecuadorian constituent for special treatment, being the first constitution to recognize it as a human and fundamental right. The research indicates that, despite the advances at the regulatory level, there is still a long way to go in terms of institutions and public resources that allow the generation of infrastructure to guarantee the right.